Layanan Bimbingan Klasikal Untuk Meningkatkan Pemahaman Bahaya Penyalahgunaan Narkoba Pada Siswa-Siswi SMPN 2 Bungku Timur - Khaerunisa, Avril Indah; Nur Wahyuni, Nur wahyuni; Bau Ratu, Bau Ratu; Puswiartika, Dhevy (Universitas Batanghari Jambi, 2024)
Â Classical Guidance Services to Raise Students' Awareness of Drug Abuse Risks at SMPN 2 Bungku Timur. Skripsi. Guidance and Counselling Study Program. Education Science Department. Teacher Training and Education Faculty. Tadulako University. Under the supervision of Nurwahyuni.This research aims to raise drug abuse risk awareness among SMPN 2Â Bungku Timur Students. The research employed a quasi-experimental method with a single-group design (without comparison) or one-group pretest-posttest design. The research subjects are 30 students. The results show that the drug abuse risks awareness among SMPN 2 Bungku Timur students before attending classical guidance services to raise awareness of drug abuse risks, out of 30 students, there were no students classified as very highly aware of drug abuse risks, no students classified as having a highly aware of drug abuse risks, 10 or 33.3% of students classified as having a low awareness of drug abuse risks, and 20 or 66.6% of students classified as having a very low awareness of drug abuse risks. Meanwhile, the understanding of drug abuse among students at SMPN 2 East Bungku after attending classical guidance services to raise awareness of drug abuse risks, out of 30 students, there were 24 or 80% of students classified as having a very highly aware of drug abuse risks, 6 or 20% of students classified as having a highly aware of drug abuse risks, no students classified as having a low awareness of drug abuse risks, and no students classified as having a very low awareness of drug abuse risks. Based on the data analysis results, it can be proven that classical guidance services influence the improvement of understanding of drug abuse hazards among students at SMPN 2 East Bungku.